Nuclear Security: Making Gender Equality a Working Reality - Muhammed Ali Alkış; Polina Sinovets (International Journal of Nuclear Security, 2023)
Gender equality is an indispensable part of both democracy and justice, and it is fundamental to peace and security worldwide. As various research on gender equality has shown, teams with diversity, equity, and inclusion achieve the best outcomes. Having gender equality and women’s presence in the workforce in nuclear fields is a requirement to contribute to peace and security discussions, adding value and sustaining policies and long-lasting positive outcomes. In this regard, the paper will discuss the importance of gender equality and why the Odesa Center for Nonproliferation has committed itself to this issue. The article also details the Odesa Center for Nonproliferation’s commitments as a member organization of the Gender Champions in Nuclear Policy.
Keywords: diversity; inclusion; equity; gender equality; nuclear; security